Entire function sharing two polynomials with its $k$th derivative - Sujoy Majumder; Nabadwip Sarkar (Mathematica Bohemica, 2024)
We investigate the uniqueness problem of entire functions that share two polynomials with their $k$th derivatives and obtain some results which improve and generalize the recent result due to Lü and Yi (2011). Also, we exhibit some examples to show that the conditions of our results are the best possible.